2003
DOI: 10.4049/jimmunol.171.4.2127
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Therapeutic Approach Targeting Articular Inflammation Using the Filarial Nematode-Derived Phosphorylcholine-Containing Glycoprotein ES-62

Abstract: Understanding modulation of the host immune system by pathogens offers rich therapeutic potential. Parasitic filarial nematodes are often tolerated in human hosts for decades with little evidence of pathology and this appears to reflect parasite-induced suppression of host proinflammatory immune responses. Consistent with this, we have previously described a filarial nematode-derived, secreted phosphorylcholine-containing glycoprotein, ES-62, with immunomodulatory activities that are broadly anti-inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
217
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 194 publications
(229 citation statements)
references
References 50 publications
10
217
0
2
Order By: Relevance
“…The immunological studies conducted show for the first time that helminth-mediated protection against autoimmunity is associated with increases in numbers of natural T-regulatory cells and that helminth infections can induce a Th2 shift in autoantigen-specific antibody production. As has been shown with other helminths, [21][22][23] live infection is not required for protection against autoimmune disease as treatment with a crude homogenate of L. sigmodontis antigens also protected against diabetes.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The immunological studies conducted show for the first time that helminth-mediated protection against autoimmunity is associated with increases in numbers of natural T-regulatory cells and that helminth infections can induce a Th2 shift in autoantigen-specific antibody production. As has been shown with other helminths, [21][22][23] live infection is not required for protection against autoimmune disease as treatment with a crude homogenate of L. sigmodontis antigens also protected against diabetes.…”
Section: Discussionmentioning
confidence: 86%
“…Indeed, animal models of arthritis, 22 type I diabetes, [12][13][14]21,24 Graves hyperthyroidism, 25 experimental autoimmune encephalitis 15,26 and colitis [16][17][18] have all been inhibited or ameliorated by infections with helminth parasites or parasite-derived products. In this study, we found that infection with filarial helminths also protects against autoimmunity.…”
Section: Discussionmentioning
confidence: 99%
“…However, in areas of the world where helminth infections are endemic, rates of autoimmune diseases such as RA remain low, leading to the hypothesis that certain helminth infections may protect against the development of autoimmunity (1). In support of this theory, we have previously shown that ES-62, a phosphorylcholine-containing glycoprotein secreted by the filarial nematode Acanthocheilonema viteae, has broad immunomodulatory activities and can exert powerful antiinflammatory action in the mouse collagen-induced arthritis (CIA) model of RA (2,3).…”
mentioning
confidence: 83%
“…Originally, it was proposed that the ability of ES-62 to inhibit disease severity in the CIA model reflected the suppression of tumor necrosis factor ␣ (TNF␣) production and associated Th1-mediated inflammation (2,3). However, it has become increasingly clear that Th17, rather than Th1, cells appear to be the pathogenic drivers of inflammation in many autoimmune conditions, including CIA and RA (4).…”
mentioning
confidence: 99%
“…5 lm cross sections were cut and stained with haematoxylin and eosin. Sections were scored in the range of 0-3 for the parameters: synovial hyperplasia, cartilage and bone erosion and fibrosis [15].…”
Section: Assessment Of Histopathological Changesmentioning
confidence: 99%